Molecular epidemiology and mechanism of Klebsiella pneumoniae resistance to ertapenem but not to other carbapenems in China - Wang, Dongliang; Wang, Minggui; He, Tianpeng; Li, Dan; Zhang, Liqin; Zhang, Dongquan; Feng, Junshuai; Yang, Wenli; Yuan, Yuan (Frontiers in Microbiology, 2022)
Ertapenem-resistant only isolate is an unusual carbapenem-resistant Klebsiella pneumoniae (CRKP). This study aimed to investigate the molecular epidemiology and mechanism underlying ertapenem resistance of K. pneumoniae strains that are sensitive to meropenem and imipenem. A total of 245 strains of CRKP were found in 697 strains of K. pneumoniae isolated from 11 grade A hospitals in China; 18 strains resistant only to ertapenem were isolated. The genotypes, phenotypes, drug resistance homology, and drug sensitivity were analyzed; moreover, the expressions of efflux pump components and outer membrane proteins were assessed. We used whole genome sequencing and analyzed drug resistance-conferring mutations in these 18 strains. Our results revealed that ertapenem resistance is likely related to ramR mutation. The function of ramR was confirmed using gene complementation to the original strain to determine the mechanism underlying ertapenem resistance of K. pneumoniae strains. In total, 7.4% of the tested CRKP strains were resistant only to ertapenem. None of these strains contained carbapenemase genes. Out of the 18 ertapenem-resistant strains, 17 expressed the efflux pump, and outer membrane protein expression was reduced or absent in 4 strains. Whole-genome sequencing revealed the presence of mutations that introduced premature stop codons into ramR in 14 strains (77.78%). When a functional copy of ramR was restored to these 14 strains, the ertapenem minimum inhibitory concentration decreased, inhibition of efflux pumps was not detected, and the expression of outer membrane protein OmpK35 either increased or was restored. Our findings reveal the existence of ertapenem-resistant K. pneumoniae exhibiting no clonal transmission between strains. Mutations in ramR were demonstrated to cause efflux pump inhibition and over-expression of outer membrane protein OmpK35 in some strains, which is implicated in ertapenem resistance only in K. pneumoniae.